Orange-fleshed sweetpotato (OFSP). Investment summary. - Stathers, T.; Mkumbira, J.; Low, Jan W.; Tagwireyi, J.; Munyua, H.M.; Mbabu, A.N.; Mulongo, G. (International Potato Center, 2015)
This OFSP Investment Summary is part of a set of three OFSP investment products: The OFSP Investment Guide that unpacks the investment opportunities along the OFSP value chain, offering a decision tool for identifying where they exist and the activities needed to transform them, including details on the human, financial and physical resources. And the OFSP Investment Implementation Guide that is targeted at those involved in the implementation of OFSP investment programmes such as local government or NGO field staff. It provides a brief overview of the reasons for investing in pro‐poor, nutrition‐sensitive agricultural growth and vitamin A deficiency reduction programmes such as the promotion of OFSP.